Leading with questions how leaders find the right solutions by knowing what to ask - Marquardt, Michael J. (San Francisco Jossey-Bass, 2014)
Many leaders are unaware of the amazing power of questions. Our conversations may be full of requests and demands, but all too often we are not asking for honest and informative answers, and we don t know how to listen effectively to responses. When leaders start encouraging questions from their teams, however, they begin to see amazing results. Knowing the right questions to ask and the right way to listen will give any leader the skills to perform well in any situation, effectively communicate a vision to the team, and achieve lasting success across the organization.
Includes bibliographical references and index.
Keywords: Leadership